2005
DOI: 10.1002/ajmg.a.30554
|View full text |Cite
|
Sign up to set email alerts
|

A novel GJA1 mutation causes oculodentodigital dysplasia without syndactyly

Abstract: Oculodentodigital dysplasia (ODDD) is a rare autosomal dominant pleiotropic disorder, caused by mutations in the Connexin 43 gene (GJA1) [Paznekas et al. (2003): Am J Hum Genet 72:408-418], which is localized to human chromosome 6q22-q23. Here, we describe the identification of a novel heterozygous missense mutation in the GJA1 gene, (H194P) in an Italian family previously reported to be affected by isolated autosomal dominant microphthalmia [Vingolo et al. (1994): J Med Genet 31:721-725]. Careful clinical re-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 10 publications
1
33
0
1
Order By: Relevance
“…Currently, twenty-eight different mutations in this gene are known to affect the phenotype (Vitiello et al 2005) by producing abnormal channel proteins that drastically reduce the permeability of various cells including osteoblasts FIGURE 4.-mRNA levels for the marker genes associated with bone development in wild-type (WT) fetuses and heterozygous (HT) and knockout (KO) mutants at different gestational times (dpc ¼ days post coitum) as determined by quantitative real-time polymerase chain reaction (RT-PCR). (A) Alterations in osteocalcin mRNA levels can be observed at 18.5 dpc in HT fetuses and at 18.5 and 19.5 dpc in the KO group.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, twenty-eight different mutations in this gene are known to affect the phenotype (Vitiello et al 2005) by producing abnormal channel proteins that drastically reduce the permeability of various cells including osteoblasts FIGURE 4.-mRNA levels for the marker genes associated with bone development in wild-type (WT) fetuses and heterozygous (HT) and knockout (KO) mutants at different gestational times (dpc ¼ days post coitum) as determined by quantitative real-time polymerase chain reaction (RT-PCR). (A) Alterations in osteocalcin mRNA levels can be observed at 18.5 dpc in HT fetuses and at 18.5 and 19.5 dpc in the KO group.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in human GJA1 are predicted to perturb the formation of functional gap junctions. To date, there are 27 reported mutations in the GJA1 gene that are linked to ODDD but, in most cases, the mechanism of action of these mutations remains unclear (Kjaer et al, 2004;Paznekas et al, 2003;Richardson et al, 2004;van Steensel et al, 2005;Vitiello et al, 2005). Recently, it was shown that the G21R and G138R mutations result in loss-of-function Cx43 and these mutants have dominant properties on wild-type Cx43 (Roscoe et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…23,[26][27][28][29]40,46,47 In the present study, OAG is present in seven of the eight individuals (87.5%) with the GJA1 mutation, which is a significantly higher association than that reported in previous studies.…”
mentioning
confidence: 45%
“…Glaucoma has been recorded in 33 of 161 patients with ODDD and GJA1 mutations but in none of the 33 patients with other conditions and GJA1 mutations. 23,[26][27][28][29][30][31]37,40,46,47 These glaucoma-associated mutations distribute randomly in the functional domains of GJA1. It total, glaucoma is reported in~17% of patients (33/194) with GJA1 mutations.…”
mentioning
confidence: 99%